Promoting physical health for people with schizophrenia by reducing disparities in medical and dental care. (11th May 2015) - Moore, S.; Shiers, D.; Daly, B.; Mitchell, A. J.; Gaughran, F.; Mitchell, Alex J; De Hert, Marc
<x xml:space="preserve">Abstract</x> Objective Acquiring a diagnosis of schizophrenia reduces life expectancy for many reasons including poverty, difficulties in communication, side‐effects of medication and access to care. This mortality gap is driven by natural deaths; cardiovascular disease is a major cause, but outcomes for people with severe mental illness are worse for many physical health conditions, including cancer, fractures and complications of surgery. We set out to examine the literature on disparities in medical and dental care experienced by people with schizophrenia and suggest possible approaches to improving health. Method This narrative review used a targeted literature search to identify the literature on physical health disparities in schizophrenia. Results There is evidence of inequitable access to and/or uptake of physical and dental health care by those with schizophrenia. Conclusion The goal was to reduce the mortality gap through equity of access to all levels of health care, including acute care, long‐term condition management, preventative medicine and health promotion. We suggest solutions to promote health, wellbeing and longevity in this population, prioritising identification of and intervention for risk factors for premature morbidity and mortality. Shared approaches are vital, while joint education of clinicians will help break down the artificial mind–body divide.